The Impact of Liquidity, Profitability and Indebtedness Indicators on Systematic Risks of Stocks in the Egyptian Real Estate Sector - Shoukry, Alaa (The Arab Journal of Administration, 2020)
This study aims to identify the effect of liquidity, profitability, and debt on the systematic risks of the Egyptian real estate stocks represented by beta coefficients for these stocks. The relationship between systematic risks for the companies under study during the period June 2014 to June 2019 and liquidity (Represented by average company turnover), profitability (represented by the average rate of return on equity) and financial leverage (represented by the average debt ratio of the company) was investigated. There was a statistically significant impact for liquidity, profitability and financial leverage on systematic risks of stocks of the Egyptian real estate companies. Multiple regression results indicated that the most influential variable on beta coefficients is the average return on equity, while the average liquidity ratio is the least influential variable. One of the three independent variables in the model (Average debt ratios) had a logical relationship with the dependent variable, where it is typically expected that systematic risk increases with increasing indebtedness. On the other hand, according to multiple regression results, the relationship between systematic risk and both liquidity and profitability was unjustified. It was recommended to use similar models as the one adopted in this study when making an investment decision considering the determinants of systematic risk (the company’s debt and liquidity and rate of return on equity). It is also recommended that companies consider the degree to which these factors affect the value of the enterprise when making decisions affecting liquidity, debt and return on equity. Further research is encouraged to discover more determinants on the systematic risk of stocks in the Egyptian real estate sector.